Association of salivary alpha-2-macroglobulin with glycemia and glycated hemoglobin in type 2 diabetes mellitus: a systematic review and meta-analysis study - Caixeta, Douglas Carvalho; Pennisi, Pedro Rogério Camargos; Moura, Douglas Vieira; Nunes, Marjorie Adriane Costa; Espindola, Foued Salmen; Blumenberg, Cauane; Paranhos, Luiz Renato; Sabino-Silva, Robinson (São Paulo Medical Journal, 2022)
BACKGROUND: Chronically elevated alpha-2-macroglobulin (A2MG) in the blood has been correlated with diabetes and the HbA1c profile; however, no systematic review has been conducted to evaluate the association of A2MG salivary levels and glycemia or HbA1c levels in diabetes mellitus type 2 (DM2) patients. OBJECTIVE: To evaluate whether A2MG salivary levels are related to the glycemia or HbA1c levels in DM2 patients. DESIGN AND SETTING: Systematic review developed at Universidade Federal de Uberlândia (UFU), Brazil. METHODS: Eight databases were used as research sources. The eligibility criteria included studies that reported data regarding mean salivary A2MG and the correlation between glycemia and/or HbA1c levels of DM2 subjects (uncontrolled and well-controlled) and non-diabetic subjects. The risk of bias of the studies selected was assessed using the Joanna Briggs Institute (JBI) critical apraisal tools for use in JBI systematic reviews. Pooled correlation coefficients were estimated using the Hunter-Schmidt method. Study estimates were weighted according to their sample size, and heterogeneity was calculated using the chi-square statistic. RESULTS: Four studies on DM2 patients were included in this systematic review after careful analysis of 1482 studies. Three studies compared A2MG with HbA1c and glycemia. Overall, the correlation between A2MG and HbA1c was strong (r = 0.838). In contrast, the correlation between A2MG and glycemia was low (r = 0.354). CONCLUSION: The strong association between HbA1C and salivary A2MG suggests that this salivary protein has the potential to be a surrogate for HbA1C, if corroboratory further evidence is obtained throughlarge-scale studies. SYSTEMATIC REVIEW REGISTRATION: CRD42020183831.